Ambient‐pressure endstation of the Versatile Soft X‐ray (VerSoX) beamline at Diamond Light Source. (17th August 2020) - Held, Georg; Venturini, Federica; Grinter, David C.; Ferrer, Pilar; Arrigo, Rosa; Deacon, Liam; Quevedo Garzon, Wilson; Roy, Kanak; Large, Alex; Stephens, Christopher; Watts, Andrew; Larkin, Paul; et al.
Abstract : The ambient‐pressure endstation of the VerSoX beamline (B07) of Diamond Light Source provides a versatile facility for soft X‐ray absorption and photoemission measurements in the mbar pressure range. A selection of typical data demonstrates the capability of the instrument to analyse details of the surface composition of solid samples and the environment gas under ambient‐pressure conditions. Abstract : The ambient‐pressure endstation and branchline of the Versatile Soft X‐ray (VerSoX) beamline B07 at Diamond Light Source serves a very diverse user community studying heterogeneous catalysts, pharmaceuticals and biomaterials under realistic conditions, liquids and ices, and novel electronic, photonic and battery materials. The instrument facilitates studies of the near‐surface chemical composition, electronic and geometric structure of a variety of samples using X‐ray photoelectron spectroscopy (XPS) and near‐edge X‐ray absorption fine‐structure (NEXAFS) spectroscopy in the photon energy range from 170 eV to 2800 eV. The beamline provides a resolving power h ν/Δ( h ν) > 5000 at a photon flux > 10 10 photons s −1 over most of its energy range. By operating the optical elements in a low‐pressure oxygen atmosphere, carbon contamination can be almost completely eliminated, which makes the beamline particularly suitable for carbon K ‐edge NEXAFS. The endstation can be operated at pressures up to 100 mbar, whereby XPS can be routinely performed up to 30 mbar. A selection of typical data demonstrates the capability of the instrument to analyse details of the surface composition of solid samples under ambient‐pressure conditions using XPS and NEXAFS. In addition, it offers a convenient way of analysing the gas phase through X‐ray absorption spectroscopy. Short XPS spectra can be measured at a time scale of tens of seconds. The shortest data acquisition times for NEXAFS are around 0.5 s per data point.